Dynamics for an electric pendulum - Aguilar-Loreto, O.; Muñoz, A.; Jiménez Pérez; A. (Revista Mexicana de Física E, 2019)
The Lagrangian formulation has been an extensive tool for the analysis of physical systems. In particular, we have applied the Lagrangian procedure to deduce the dynamics and stability for an electric pendulum system. We have considered two cases, a repulsive and attractive electric interactions as perturbations to the classical simple pendulum model. We study both cases, the repulsive and attractive electric interactions that can be considered as perturbations to the classical simple pendulum model. We have contrast both situations studying their restrictions, phase trajectories and stability points for this purpose.